Optimasi Pengambilan Keputusan Budidaya Padi Organik Dengan Model Metriks Terboboti: Studi Kasus Di Desa Afia, Kota Gunungsitoli - zega, Krisnawati; Khoiriyah (CV. SINAR HOWUHOWU, 2025)
This study developed a weighted matrix model to assist organic rice farmers in Desa Afia, Gunungsitoli City, in making more efficient and sustainable decisions. The model integrates key factors such as soil quality, climate, resource availability, and economic aspects. Analysis results indicate that the model can identify optimal cultivation strategies that enhance crop yields and profitability while considering environmental sustainability. This model integrates various key factors that influence the productivity and sustainability of organic agriculture, including soil quality (pH, organic matter content, texture), climate conditions (rainfall, temperature, sunshine), resource availability (water, organic fertilizer, labor), and economic aspects (rice selling price, production costs). Analysis using this model demonstrates its ability to identify optimal cultivation strategies that can enhance crop yields and farmer profitability while minimizing negative environmental impacts. These optimal strategies include selecting superior varieties, applying appropriate organic fertilization techniques, efficient water management, and integrated pest management. This research makes a significant contribution to the development of appropriate technology to support sustainable organic agriculture in the region and can be replicated in other areas with similar characteristics.